Guidebook of applied fluvial geomorphology - Sear, David (Thomas Telford, 2010)
The authors use their extensive practical experience to provide a thorough understanding of geomorphology in the river environment, discuss how these principles can be integrated with projects and point the reader towards where to seek further information and advice.